Semiotic Analysis: Essential Moral Study in the Film "The Sinking of the Van der Wijck Ship - Lubis, Muhammad Akbar Affandi; Tanjung, Muaz (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This article aims to explore and understand the use of signs and symbols in the film "The Sinking of the Van Der Wijck Ship" as tools for communicating moral and ethical messages. Through a semiotic approach, this study highlights how visual and narrative elements contribute to the formation and understanding of cultural hegemony in Indonesia, based on Antonio Gramsci's theory of cultural hegemony. The urgency of this research arises from the need to understand how films influence and shape social and cultural perspectives, particularly in the context of the Minangkabau community, which is rich in tradition and customs. The methodology used is qualitative descriptive, with data collected through observation and in-depth analysis of the film's narrative and the interpretation of the symbols used. The results of the study show that this film functions not only as an entertainment medium but also as a powerful moral education tool that communicates the conflict between traditional and modern values through the rich use of symbols. The discussion in this article emphasizes how the film depicts the struggle for hegemony in society, highlighting the conflict between personal desires and social demands. This research provides new insights into the role of media in influencing and understanding social and cultural dynamics, offering a broader perspective on how visual narratives can impact public understanding of social and cultural issues.